Preferencias de los propietarios e intervención pública: el caso de las dehesas de la comarca de Monfragüe - Campos Palacín, P.; Mariscal Lorente, P. J. (Investigación Agraria: Sistemas y Recursos Forestales, 2003)
The public have an increasing interest in Dehesa environmental services (recreation, option and existence values). The growing Government incentives on environmental friendly agricultural practices have given a new opportunity for private economics of natural and environmental resources in Dehesa. This work presents the results from a Delphi questionnaire on owners’ preferences and demands of compensations for undertaking environmental conservation and improvement measures in Dehesa of Monfragüe shire. The private owners of Dehesa are investors that have, at the same time, commercial aims and private environmental services autoconsumption preferences. A contingent valuation questionnaire has been applied to a group of Dehesa ’ owners to measure the maximum willingness to pay (WTP) —to accept losses— of commercial capital income against the maintenance of private environmental services autoconsumption. The Delphi results show that owners’attitude is in favour to follow the environmental friendly agricultural practices, when the Government incentives are higher than the losses of commercial capital income plus a risk premium. The value of owners’ autoconsumption measured by the WTP question from the contingent valuation gives an autoconsumption profitability rate from 1% to 5% of the total market value of the Dehesa.
Keywords: Contingent valuation; Dehesa; Delphi technique; environmental and agroforestry practices; environmental autoconsumption services; Hicksian income

Preferencias de los propietarios e intervención pública: el caso de las dehesas de la comarca de Monfragüe - CAMPOS PALACIN, P; Mariscal Lorente, P J (Investigación Agraria: Sistemas y Recursos Forestales, 2003)
The public have an increasing interest in Dehesa environmental services (recreation, option and existence values). The growing Government incentives on environmental friendly agricultural practices have given a new opportunity for private economics of natural and environmental resources in Dehesa. This work presents the results from a Delphi questionnaire on owners’ preferences and demands of compensations for undertaking environmental conservation and improvement measures in Dehesa of Monfragüe shire. The private owners of Dehesa are investors that have, at the same time, commercial aims and private environmental services autoconsumption preferences. A contingent valuation questionnaire has been applied to a group of Dehesa ’ owners to measure the maximum willingness to pay (WTP) —to accept losses— of commercial capital income against the maintenance of private environmental services autoconsumption. The Delphi results show that owners’attitude is in favour to follow the environmental friendly agricultural practices, when the Government incentives are higher than the losses of commercial capital income plus a risk premium. The value of owners’ autoconsumption measured by the WTP question from the contingent valuation gives an autoconsumption profitability rate from 1% to 5% of the total market value of the Dehesa.
Keywords: Contingent valuation; Dehesa; Delphi technique; environmental and agroforestry practices; environmental autoconsumption services; Hicksian income